2012
DOI: 10.1063/1.3684247
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of microwave rectification effects in electrically detected magnetic resonance measurements

Abstract: Spin-dependent transport properties of micro- and nano-scale electronic devices are commonly studied by electrically detected magnetic resonance (EDMR). However, the applied microwave fields in EDMR experiments can induce large rectification effects and result in perturbations of the device bias conditions and excessive noise in the EDMR spectra. Here we examine rectification effects of silicon metal-oxide-semiconductor field-effect transistors exposed to X-band microwave irradiation and show that the rectific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…After stripping the e-beam resist, both sets of devices were metallized with 300 nm of thermally evaporated Al over the source/drain and n + poly-Si gate. Al was evaporated over the gate to avoid loading the ESR resonator by the resistive poly-silicon [25] and to accelerate the passivation of interface defects. [26] Thermal evaporations were chosen over e-beam evaporations in this process as the latter method creates X-rays that can further damage the Si/SiO 2 interface.…”
mentioning
confidence: 99%
“…After stripping the e-beam resist, both sets of devices were metallized with 300 nm of thermally evaporated Al over the source/drain and n + poly-Si gate. Al was evaporated over the gate to avoid loading the ESR resonator by the resistive poly-silicon [25] and to accelerate the passivation of interface defects. [26] Thermal evaporations were chosen over e-beam evaporations in this process as the latter method creates X-rays that can further damage the Si/SiO 2 interface.…”
mentioning
confidence: 99%
“…2(c)) diminishes the achievable oscillation amplitudes. We also found increased significance of microwave rectification effects at low bias electric fields; improved sample designs optimized for microwave resonator-based ESR measurements can be used to reduce such detrimental rectification effects [22], and allow high microwave power pulsed ESR measurements to be performed on the devices.…”
Section: Channel Detectormentioning
confidence: 82%
“…It was successfully applied to a wide variety of material systems, ranging from inorganic to organic semiconductors and to devices such as thin film solar cells or transistors. [1][2][3][4][5][6][7] One of the major advantages of EDMR compared to conventional electron spin resonance (ESR) is its higher sensitivity. A systematic study of the sensitivity of continuous wave EDMR (cwEDMR) at liquid helium temperature using phosphorus-doped silicon samples has shown that at present cwEDMR is able to detect as few as 100 spins.…”
Section: Introductionmentioning
confidence: 99%